2023
DOI: 10.2196/46753
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Social Capital to Address Isolation and Loneliness in Long-Term Care Facilities During the COVID-19 Pandemic: Systematic Review of Research on Information and Communication Technologies

Idrissa Beogo,
Drissa Sia,
Stephanie Collin
et al.

Abstract: Background The COVID-19 pandemic has disproportionately and severely affected older adults, namely those living in long-term care facilities (LTCFs). Aside from experiencing high mortality rates, survivors were critically concerned by social isolation and loneliness (SIL). To address this serious public health concern and stay connected with LTCF residents, information and communication technology (ICT) platforms (eg, video calls) were used as an alternative to maintaining social interactions amid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Coe and Werner’s analysis of population health survey data found that family caregivers of long-term care residents contributed 37.4 h of care per month on average, which is roughly equivalent to an extra full-time shift of paid providers per month [ 16 ]. The long-term care staffing shortages that existed prior to the pandemic [ 8 , 24 ] were exacerbated by restrictions on what family caregivers could do [ 17 ], leading to increased work to follow COVID-19 policies [ 23 , 25 ] and trying to meet residents’ increased care and socioemotional needs [ 16 , 17 ] while supporting family visitations through window visits or with technology such as iPads or ZOOM [ 6 , 26 , 27 ]. The pandemic reinforced that family involvement in long-term care is essential for promoting person-centered care, improving the well-being of residents, and fostering a collaborative approach to caregiving [ 5 , 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coe and Werner’s analysis of population health survey data found that family caregivers of long-term care residents contributed 37.4 h of care per month on average, which is roughly equivalent to an extra full-time shift of paid providers per month [ 16 ]. The long-term care staffing shortages that existed prior to the pandemic [ 8 , 24 ] were exacerbated by restrictions on what family caregivers could do [ 17 ], leading to increased work to follow COVID-19 policies [ 23 , 25 ] and trying to meet residents’ increased care and socioemotional needs [ 16 , 17 ] while supporting family visitations through window visits or with technology such as iPads or ZOOM [ 6 , 26 , 27 ]. The pandemic reinforced that family involvement in long-term care is essential for promoting person-centered care, improving the well-being of residents, and fostering a collaborative approach to caregiving [ 5 , 10 , 14 ].…”
Section: Introductionmentioning
confidence: 99%